Circadian Host-Microbiome Interactions in Immunity - Butler, Thomas D.; Gibbs, Julie E. (Frontiers in Immunology, 2020)
The gut microbiome plays a critical role in regulating host immunity and can no longer be regarded as a bystander in human health and disease. In recent years, circadian (24 hour) oscillations have been identified in the composition of the microbiota, its biophysical localisation within the intestinal tract and its metabolic outputs. The gut microbiome and its key metabolic outputs, such as short chain fatty acids and tryptophan metabolites contribute to maintenance of intestinal immunity by promoting barrier function, regulating the host mucosal immune system and maintaining the function of gut-associated immune cell populations. Loss of a rhythmic host-microbiome interactions disrupts host immunity and increases risk of inflammation and metabolic complications. Here we review factors that drive circadian variation in the microbiome, including meal timing, dietary composition and host circadian clocks. We also consider how host-microbiome interactions impact the core molecular clock and its rhythmic outputs in addition to the potential impact of this relationship on circadian control of immunity.